Constructing a grounded theory of grit in sport: understanding the development and outcomes of long-term passion and perseverance in competitive athletes - Cormier, D. L.; Jørgensen, H.; Ferguson, L. J.; Gyurcsik, N. C.; Briere, J. L.; Kowalski, K. C. (Qualitative Research in Sport, Exercise and Health, 2024)
To be successful, athletes are expected to overcome the many setbacks and demands of sport throughout the entirety of their competitive career. Grit - or passion and perseverance over long terms - has been linked to positive outcomes in the sport domain, but progress in the field has been hindered by a lack of sufficient theory. The purpose of this study was to construct a grounded theory of competitive athletes` grit in sport, and constructivist grounded theory methodology was adopted. Twenty-seven participants (14 women, 13 men; 22 athletes, 5 coaches) involved in competitive sport participated in individual semi-structured interviews. Data analysis involved an iterative process of initial coding, focused coding, axial coding, and theoretical integration. Results showed grit to be a malleable dispositional tendency that was formed over time as athletes amassed significant sport experiences. With the encouragement from supportive others, athletes would adopt adaptive cognitions about success and failure. These cognitions would then develop into a propensity to identify and strive towards long-term goals in sport. Participants described grit as leading to several outcomes, including sport-specific goal achievement, adaptive outcomes, and maladaptive outcomes. Our research advances the study of grit in sport by providing researchers and practitioners a deeper understanding of the processes that encapsulate competitive athletes` sport-specific grit. Implications for practice (e.g., how sport support persons might foster grit in athletes) and recommendations for future research (e.g., improving the measurement of grit in sport) are also discussed.